Implication of Increased Serum IL-31 for Primary Biliary Cholangitis. (18th August 2021) - Mu, Ning; Lin, Feng; Jiang, Zhiguo; Liang, Yan; Yang, Zaixing
ABSTRACT: Interleukin-31 (IL-31) has diverse biological functions. Increased IL-31 has been found in some skin and autoimmune diseases. There has been no study reporting the association between IL-31 and primary biliary cholangitis (PBC). This study was designed to determine serum IL-31 level and to explore its diagnostic value for PBC as well as the association of IL-31 with inflammatory and fibrotic progression. 60 PBC patients, 32 age- and sex-matched patients with chronic hepatitis B (CHB) and 30 age- and sex-matched healthy controls (HC) were recruited. The sera were detected for IL-31, IL-4, interferon gamma (IFN-γ), IL-17 and other laboratory indicators. Serum IL-31 levels were significantly higher in PBC patients (median, IQR, 20.6, 16.7–26.2, pg/ml) than CHB patients (median, IQR, 11.3, 8.0–13.0, pg/ml) and HC (median, IQR, 11.0, 10.0–12.2 pg/ml) ( P < .001). Serum IL-31 performed well for identifying PBC, especially for antimitochondrial antibodies (AMA)-negative PBC with AUC of 0.900, optimal cutoff value of 13.6 pg/ml, sensitivity of 87.5% and specificity of 83.9%. Serum IL-31 was positively correlated with platelet count (r = 0.368, P = .004), but negatively with FIB4 (r = −0.307, P = .017) and histological stages (r = −0.364, P = .004) in PBC patients. It was also significantly correlated with IFN-γ (r = 0.404, P = .001) and IL-4 (r = 0.291, P = .026), but not with IL-17 (r = 0.151, P = .259) in PBC patients. Serum IL-31 is increased in and may be a useful marker for PBC, in particular, for AMA-negative PBC. Furthermore, it is inversely associated with fibrotic progression of PBC.